Suicidal ideation and attempts in population-based samples of women: temporal changes between 1989 and 2015 - Solveig Lövestad; Jesper Löve; Marjan Vaez; Margda Waern; Gunnel Hensing; Gunilla Krantz (BMC, 2019)
Abstract Background Little is known about temporal changes in the prevalence of self-reported suicidal ideation and attempts within general populations of women. The aim of this study was to assess the prevalence of self-reported suicidal ideation and attempts over a 26 year period (1989-2015) among women from the general population aged 20-49 years. A further aim was to investigate associations between sociodemographic factors and lifetime suicidal ideation over this study period. Methods A total of 2072 structured personal interviews were performed with a stratified population-based sample of women between 1989 and 2015. Questions about lifetime suicidal ideation and attempts as well as sociodemographic factors were assessed at four data collection waves. Lifetime prevalence of suicidal ideation and attempts were compared through analysis of differences between two independent proportions and their 95% Confidence Intervals (CI). Associations between sociodemographic factors and lifetime suicidal ideation were estimated by weighted odds ratios (OR). Results Women aged 20-30 years reported higher lifetime prevalence of suicidal ideation in 2013-2015 compared to 1989-1991 (45 and 33% respectively). Rates of lifetime suicide attempts remained similar between these time points (3.5 and 3.1% respectively). Women aged 31-49 years reported higher lifetime prevalence of suicidal ideation in 2013-2015 compared to 2000-2002 (35.4 and 23.1% respectively). In this age group, lifetime suicide attempts increased from 0.0% in 2000-2002 to 3.6% in 2013-2015. Women aged 20-30 years who were single, unemployed or had low educational attainment had higher OR of lifetime suicidal ideation compared to the reference categories in most of the study waves. In 2013-2015, young students had lower OR of lifetime suicidal ideation (OR 0.34; 95% CI 0.17-0.69) compared to those with employment. Women aged 31-49 years, who were single, had higher OR of lifetime suicidal ideation (OR 2.61; 95% CI 1.06-6.44) than married, cohabiting women and this was observed in 2013-2015. Conclusion The results raise a general concern about an increasing trend in suicidal ideation among young and middle-aged women. The current study expands on previous research by demonstrating that sociodemographic factors may show changing patterns in the associations with lifetime suicidal ideation over time.